Qualitative Parental Perceptions of a Paediatric Multidisciplinary Team Clinic for Prader-Willi Syndrome - Jennifer S. Cox (Galenos Yayincilik, 2021)
Objective:This preliminary review was conducted to inform the design of a new service to support families with children with Prader-Willi syndrome (PWS). Families were invited to attend a pilot clinic at a hospital outpatient department, comprising appointments with a multi-disciplinary team (MDT).Methods:Following the clinic, families (n=6) were invited to take part in semi-structured qualitative interviews that were audio-recorded, transcribed and analysed using thematic analysis.Results:Families reported that the clinic offered enhanced support in the following categories: integrated care; professional input; signposting to social support (respite and financial); connection with the wider PWS community; and behavioural support.Conclusion:This is the first paper that documents the parental perspective of an MDT clinic for children with PWS. The families felt an MDT clinic was superior to current care, offering more convenient access to an enhanced service, which would provide integrated and consistent care for their children’s diverse, challenging and changing needs.